Review of Published Chain Information System Research - Storer, Christine; Trienekens, J.; Beulens, A.; Quaddus, Mohammed (Wageningen Publishers, 2006)
This paper provides a review of the literature on chains and networks that examine inter-organisational information systems used to manage chains of organisations. Difficulty was found in finding out how organisations exchanged information to manage relationships with customers and suppliers in chains. Most research publications found were based on case studies and few looked at chains of three or more organisations. Substantial research over a greater time period was found on dyadic buyer-seller inter-organisational relationships (companies and either their customers or suppliers). Conclusions are made about how to describe inter-organisational information systems and suggestions for empirical chain research using comparative pairs for data collection and analysis.